2010
DOI: 10.1186/1748-5908-5-51
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' intentions to use clinical guidelines: a survey using the theory of planned behaviour

Abstract: BackgroundFinnish clinical guidelines are evolving toward integration of knowledge modules into the electronic health record in the Evidence-Based Medicine electronic Decision Support project. It therefore became important to study which factors affect professionals' intention to use clinical guidelines generally in their decision-making on patient care. A theory-based approach is a possible solution to explore determinants of professionals' behaviour. The study's aim was to produce baseline information for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 44 publications
13
113
2
1
Order By: Relevance
“…20 , 22 For example, Kortteisto et al have shown that the most important factor in the prediction of doctors' intention to use clinical practice guideline was perception of control, whereas the most important factor in the prediction of nurses' intention to use it was subjective norm. 20 Rashidian and Russel have shown that physicians' intention to respect the guidelines of recommended prescriptions was explained by perception of control and attitude, but not by subjective norm. 22 However, these results should be compared to our results with caution, because the targeted behaviours are different and are studied in different contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 , 22 For example, Kortteisto et al have shown that the most important factor in the prediction of doctors' intention to use clinical practice guideline was perception of control, whereas the most important factor in the prediction of nurses' intention to use it was subjective norm. 20 Rashidian and Russel have shown that physicians' intention to respect the guidelines of recommended prescriptions was explained by perception of control and attitude, but not by subjective norm. 22 However, these results should be compared to our results with caution, because the targeted behaviours are different and are studied in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,[18][19][20][21] For example, Kortteisto et al indicate that subjective norms were a key factors in the prediction of healthcare professionals' intention to use clinical practice guidelines in their speciality field to make decisions concerning patients care. 20 Foy et al indicate that subjective norms contribute to predict healthcare professionals' intention to determine patients' knowledge, to use explicit terminologies and to investigate the meaning of diagnoses for patients. 14 Wu et al found that subjective norms had the biggest effect on healthcare professionals' intention to use a report system of unwanted events.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of KTE research is in the medical and nursing literature [31] and research into the allied health professions has focussed on physiotherapists and occupational therapists [35,36]. This is particularly problematic given that the factors affecting CPG implementation have been found to vary with profession [37], and because speech pathologists have distinctive responsibilities for the swallowing and communication function of stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if people are given an adequate amount of control over a given behaviour, it is expected that they will execute their intentions when the opportunity emerges 6 . In this study, TPB is used as a basis for the study of care professionals [7][8][9], but as it leaves little space for the affective aspects of behaviour, an aspect which in healthcare is an important part of intention, we have chosen to include the factor 'moral norm' to the conceptual model used in this study ( Figure 2). Given this conceptual model, there are two relevant factors: (1) the intention of the care professional to optimally use the DLS, and (2) the control the care professionals believe to perceive in order to come to the execution of certain behaviour.…”
Section: Accepted Manuscriptmentioning
confidence: 99%